(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
As the caretakers of democracy, political parties are very important actors in the promotion of women’s inclusion in democratic institutions. They have shown interest in women’s problems in the last few decades. Members of political parties regularly create supporting groups around different issues and demographics, like Youth wings, Students wings and Women wings. Women wings are the central core of politics. For this reason these wings are the main entrypoint of women to participation in political activities. These bodies are generally aimed at supporting women who run for office and or seek senior leadership arrangements in the party, along with influence the party’s agenda with respect to policies concerning women. Political party wings and parliamentary bodies independently play a major role in improving women’s political representation and leadership, they can achieve their goals successfully when they strategically work together even in a challenging political climate.